On the Unutilised Capacity in a Production-Storage System - PARTHASARATHY, P. R. (Institutional Knowledge at Singapore Management University, 1987)
A A one-product one-machine production/inventory problem in which the machine is subject to failure, is considered. The product is stored in an inventory of finite capacity. When the machine is operable, it produces at a rate α greater than the demand rate β, until the inventory becomes full and thereafter it produces at the demand rate. This stepping down of the rate of production results in the under-utilisation of the machine. The under-utilisation of the machine and the demand not met are analysed; special cases are considered. Cost analysis is also indicated.